﻿Comparative study of the chemical composition of Trigonella foenum-graecum L. essential oil - Vanya Nalbantova; Niko Benbassat; Cédric Delattre; Velislava Todorova; Yoana Georgieva; Paolina Lukova; Stanislava Ivanova; Kalin Ivanov; Diana Karcheva-Bahchevanska (Pharmacia, 2023)
Fenugreek is a well-known aromatic plant. Its leaves and seeds are commonly used for their many health benefits and the species is cultivated worldwide. For the first time, essential oils (EOs) from seeds of the Bulgarian and Indian populations were obtained by secondary distillation of hydrolat to extract the residual essential oil therein. They were analyzed by gas chromatography-mass spectrometry and the chemical composition of the two samples was compared. Thirty-six compounds were identified and although the results showed some differences in the component composition of the two essential oils, the major constituents identified in both oils were cubenol, γ-n-amylbutyrolactone and palmitic acid. Moreover, oxygenated sesquiterpenes were the predominant fraction in Bulgarian and Indian seeds oils. Information is limited regarding menthol and γ-n-amylbutyrolactone, which were found in the present study in both oils. The performed analysis confirmed the presence of phytol in fenugreek seeds regardless of the extraction method of the essential oil.